On the move : mobile learning for development - Kinuthia, Wanjira; Marshall, Stewart (Emerald Publishing Limited : Information Age Publishing, 2013)
This book integrates research, action research, best practice and case studies detailing how some educators have embraced the opportunities afforded by mobile learning. In particular, it brings together a range of scenarios, solutions and discussions relating to mobile learning in development and other resource challenged contexts.The book will appeal to elected public/government representatives, public service agencies, community groups, regional development bodies, researchers, educational technologists and others interested in mobile learning. Students on senior undergraduate or postgraduate courses in educational technology, education, development studies, information technology, information systems, business, health, and social work will find this book useful in their studies related to the application of mobiles in learning and development.
Keywords: Mobile communication systems in education -- Developing countries.; Education -- Distance, Open & Online Education.; Adult education, continuous learning.; Open learning, distance education.; elektronické knihy; electronic books